Splenectomy and removal of bilateral huge chocolate cyst with ovarian preservation - Gurung, G.; Rana, A.; Joshi, P.; Pradhan, P. (Journal of Institute of Medicine Nepal, 2007)
Case report: An unusual discovery of exceptionally large, bilateral chocolate (endometriotic) cysts of ovaries amidst dense pelvic adhesion and thick peritoneal collection due to occasional spill from the cyst in a young adolescent, encountered during spleenectomy performed for idiopathic thrombocytopenia is reported.